2022
DOI: 10.1007/s00204-022-03251-z
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual variation in chlorpyrifos toxicokinetics characterized by physiologically based kinetic (PBK) and Monte Carlo simulation comparing human liver microsome and Supersome™ cytochromes P450 (CYP)-specific kinetic data as model input

Abstract: The present study compares two approaches to evaluate the effects of inter-individual differences in the biotransformation of chlorpyrifos (CPF) on the sensitivity towards in vivo red blood cell (RBC) acetylcholinesterase (AChE) inhibition and to calculate a chemical-specific adjustment factor (CSAF) to account for inter-individual differences in kinetics (HKAF). These approaches included use of a Supersome™ cytochromes P450 (CYP)-based and a human liver microsome (HLM)-based physiologically based kinetic (PBK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In the present study, the kinetics for the microsomal clearance of aloe-emodin and its conversion to rhein were quantified using pooled human liver microsomes. Future studies could quantify the effect of variation in CYP-mediated clearance and bioactivation of aloe-emodin by combining our PBK modeling with Monte Carlo simulations that select the respective kinetic parameters from the distribution describing the probability of the values for V max and K m within the human population . The sensitivity analysis presented in the present study reveals that especially variability in V max and K m for conversion of aloe-emodin to rhein will be of influence (Figure S8).…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, the kinetics for the microsomal clearance of aloe-emodin and its conversion to rhein were quantified using pooled human liver microsomes. Future studies could quantify the effect of variation in CYP-mediated clearance and bioactivation of aloe-emodin by combining our PBK modeling with Monte Carlo simulations that select the respective kinetic parameters from the distribution describing the probability of the values for V max and K m within the human population . The sensitivity analysis presented in the present study reveals that especially variability in V max and K m for conversion of aloe-emodin to rhein will be of influence (Figure S8).…”
Section: Discussionmentioning
confidence: 89%
“…Following exposure to organophosphate pesticides, liver CYP450s-mediated bioactivation and detoxification take place . For FNT, the bioactivation instead of its detoxification is found to be more efficient in rats and humans (Figure ), as opposed to the results found for chlorpyrifos and diazinon. , Several CYP450s including 1A2, 2B6, 2C19, and 3A4 were reported to participate in both bioactivation and detoxification of organophosphate pesticides, , while specific information on the CYP450s involved in FNT metabolism is limited. Levi et al purified two chemically induced isoforms (named as P-450 PB and P-450 BNF) from livers of mice that were pretreated orally or intraperitoneally with phenobarbital (PB) or β-naphthoflavone (BNF), inducers for CYP2B9/10 and 1A1/2 in mice, respectively. , In their study, P-450 PB and P-450 BNF were reported to produce higher amounts of FNO compared to MNP production.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolysis efficiency of PON1 toward oxons varies among organophosphate pesticides, as a slight change in their leaving groups can affect the orientation of the oxon in the active site and hence their conversion . For example, the PON1-catalyzed detoxification of methyl paraoxon was found to be less efficient than that of CPO in both rats and humans. , This observation is in agreement with the lower PON1 catalytic efficiency toward FNO (Table S4) as compared to that of CPO, considering that methyl paraoxon and FNO are highly similar in structure. Similar to CYP450s, the activity of PON1 shows interindividual differences, while relevant information is limited on how it will affect the resulting toxicity among individuals following acute FNT exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations